KAJIAN PERUBAHAN STATUS FOSFOR TANAH AKIBAT PEMBERIAN BOKASHI KULIT BUAH KAKAO PADA INSEPTISOLS PALOLO - Imam Wahyudi (Universitas Tadulako, 2010)
High content of aluminium and low P availability in Inceptisols are the important limiting factors for crop production. Hence, important efforts on management of Inceptisols are the increasing in P availability for crop demand. Cacao fruit skin bokashi is a source of organic matter used to improve the soil, although using bokashi as organic fertilizer is still not yet have full attention. A study that was aimed to elucidate roles of cacao fruit skin boakshi on Al concentration, and soil P status in an Inceptisols was conducted in a laboratorium. Five treatments consisting of the rates of the bokashi (10, 20, 30, 40 and 50 ton/ha) and one control (no bokashi added) were arranged in a completely randomized design with three replicates. Results of the experiment showed that the application of 30 t ha-1 cacao fruit skin bokashi significantly increased soil pH, soil organic-C, P-total and P availability, and reduced Alexch concentration. However, the soil pH and P availability were reduced at the rate of bokashi of 40 and 50 t ha-1, but Alexch concentration was increased.